Exploration and Connotation Analysis of Social Capital Theory: Also Talk about Several Misunderstanding of Concept Cognition - Wang, Yingxue; Zhang, Jiliang (Journal of Theory and Practice of Humanities Science, 2023)
In academic research, the understanding and grasp of concept is the premise of concept application. Especially for social capital, an abstract concept that can be used as an analytical and explanatory tool, the accurate grasp of the concept is particularly important. Since the establishment of social capital theory in the 1980s, studies on social capital theory and practical application have emerged one after another at home and abroad. After careful reading, we will find that some of these achievements have fallen into some misunderstandings in the concept understanding and concrete use of social capital. [1] This will not only affect our thinking on the functional mechanism of social capital, but also affect our analysis and judgment on the existence of social capital itself and its practical value. Therefore, we think it is necessary to systematically comb the theoretical basis, concept and connotation of social capital, so as to restore the original appearance of social capital.